ANALISIS PERKEMBANGAN KEMANDIRIAN TERHADAP KEMAMPUAN PENYESUAIAN DIRI SISWA KELAS I DAN KELAS V - Endah Kusumaningrum, Yuris Indria Persada; Eka Yanti, Yulia; Azzahra Bil Haqqi, Nabila; Royani, Ida (STKIP Subang, 2021)
The Effect of Independence Development to Self-Adjustment Abilities of 1st Grade and 5th Grade Students. The development of independence and adaptation ability is an important thing and must be passed by every student’s development. In this study, research was conducted on 5th grade students and 1st grade student. The result is the 5th grade student had better development of independence and self-adjustment abilities than 1st grade student.